Spatial distribution of manatees in southern Gulf of Mexico coastal plain - León D Olivera-Gómez, Leon D Olivera-Gómez; Jiménez-Domínguez, Darwin; Morales-Vela, Benjamín; García-Herrera, José Luis (Ecosistemas y Recursos Agropecuarios, 2022)
The manatee is an herbivorous aquatic mammal, considered endangered in Mexico, that inhabits the Atlantic plain coasts of Mexico. The lower basins of the Grijalva and Usumacinta rivers has long been proposed as an important nucleus of distribution and abundance in Mexico. To resume information of manatees on a map, based on the connectivity of water courses, lagoons and flood plains over these two basins, in this study we analyzed historical, 1980 to 2000, and recent, 2000 to 2019, information, grouping from opportunistic observations to data resulting from point surveys and tracking projects. There are zones where the coverage of studies has been insufficient or with a lack of reports and other areas where the amount and quality of multiple information highlight its current importance. The coverage of protected areas is shown as an instrument for the conservation plans of the species.